Influence of temperature on microstructure, crystallographic texture and mechanical properties of EN AW 6016 alloy during plane strain compression. (March 2021) - Ghosh, Arkajit; Roy, Avinava; Ghosh, Abhishek; Ghosh, Manojit
Abstract: The use of Al-Mg-Si alloys has increased significantly in automobile and aerospace industries during the past few decades, and improving the formability of the alloy has always been under focus for various applications. Plane strain compression (PSC) tests have been conducted for EN AW 6016 naturally aged (T4) alloy at different temperatures (room temperature, 150 °C and 250 °C), at a particular strain rate (0.1 s −1 ). The samples exhibited a decreasing pattern of flow properties (yield strength and work hardening rate) and increasing anisotropy with temperature. The reasons for the changes in flow behaviour with temperature were explained with the help of finite element modelling (FEM). Work hardening behaviour at different stages of stress was investigated and correlated with the microstructure. Microstructural characterization has been performed using electron backscattered diffraction (EBSD), and scanning electron microscopy (SEM) based Gallium Enhanced Microscopy (GEM) techniques with an aim to reveal the substructure development due to imposed deformation at different temperatures. Calculation of macro-texture was performed using X-Ray Diffraction (XRD) technique in order to observe the changes in crystallographic texture before and after deformation. A mathematical comparative analysis indicates the contribution of different texture components towards the variation in flow properties. Considerable increment in volume fraction of Goss texture at 250 °C has been found to have a significant impact on formability.